2019
DOI: 10.1101/622738
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myosin motor domains carrying mutations implicated in early or late onset Hypertrophic Cardiomyopathy have similar properties

Abstract: Hypertrophic Cardiomyopathy (HCM) is a common genetic disorder that typically involves left ventricular hypertrophy and cardiac hypercontractility. Mutations in β cardiac myosin heavy chain (β-MyHC) are a major cause of HCM, but the specific mechanistic changes to myosin function that lead to the disease remain incompletely understood. Predicting the severity of any single β-MyHC mutation is hindered by a lack of detailed evaluation at the molecular level. In addition, since the cardiomyopathy can take 20 or m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 62 publications
(84 reference statements)
9
27
0
Order By: Relevance
“…Additionally, Cassell and Tobacman 65 indicated that myosin-heads increase the affinity of Tpm for F-actin and Tpm enhances myosin binding to M-state actin, possibly through direct myosin-Tpm interactions 66,67 . Therefore, the M305L mutation could affect the S1 catalytic cycle through effects on F-actin-Tpm-myosin associations, and promote excessive force production and HCM 68 . However, these Tpm-myosin interactions were not tested in our in silico studies, nor do our experimental results, acquired from mutant IFMs, necessarily suggest they are impacted.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Cassell and Tobacman 65 indicated that myosin-heads increase the affinity of Tpm for F-actin and Tpm enhances myosin binding to M-state actin, possibly through direct myosin-Tpm interactions 66,67 . Therefore, the M305L mutation could affect the S1 catalytic cycle through effects on F-actin-Tpm-myosin associations, and promote excessive force production and HCM 68 . However, these Tpm-myosin interactions were not tested in our in silico studies, nor do our experimental results, acquired from mutant IFMs, necessarily suggest they are impacted.…”
Section: Discussionmentioning
confidence: 99%
“…k0,  and step size were measured from single molecules using the HFS technique. kcat and Kapp were measured using a colormetric actin-activated ATPase assay and were previously reported [16]. Unloaded velocities were measured by the motility assay with actin filaments.…”
Section: The P710r Mutation Reduces Load Sensitivity and Step Size Ofmentioning
confidence: 99%
“…Many MYH7 mutations examined in biophysical and physiological studies have been found to cause changes in individual kinetic steps that impact the fraction of intermediates in force producing states. While some confer apparent hypercontractile activity, no uniform kinetic signature for HCM has emerged from these studies (e.g., [6][7][8]). Thus, it is not clear that all HCM mutations in the myosin motor conform to the hypercontractile hypothesis.…”
Section: Introductionmentioning
confidence: 99%